Efektivitas pendekatan konseling cognitive behavior dengan teknik self-management untuk meningkatkan kemandirian belajar peserta didik di sekolah menengah kejuruan - Rusmini, Made; Suarni, Ni Ketut; Dharsana, I Ketut (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study aims to determine the application of cognitive behavior counseling services with self-management techniques to increase the learning independence of class X hospitality students at SMK Negeri 1 Singaraja. This experimental research uses data collection techniques with random sampling techniques. The analysis technique used is in the form of parametric statistical analysis using the Paired-Sample T-Test. This research method aims to determine the influence of cognitive behavior counseling with self-management techniques in increasing student learning independence. The design of this study was the Non-Equivalent Control Group Design which was carried out on students in the control class and the experimental class. The focus of this research is on the changes produced by cognitive behavior counseling services with self-management techniques to increase student learning independence with data collection techniques used, namely questionnaires. Based on the significance test, it is found that the significance value is 0.000 where 0.000 ˂ 0.05, where the Application of Cognitive Behavior Theory with Self Management Techniques is effective for Increasing Student Learning Independence at SMK Negeri 1 Singaraja